Peningkatan Pemahaman Konsep Sifat-Sifat Bangun Datar Dengan Metode Guided Discovery Learning di Kelas III SDN Sananwetan 2 Kota Blitar - Ariadi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2021)
In learning mathematics, the teacher provides opportunities for students to carry out activities of finding and investigating patterns and to determine relationships. Activities can be carried out through experiments to find sequences, differences, comparisons, groupings, and so on and provide opportunities for students to find relationships between understanding one another. In fact, the Mathematics learning material on the Characteristics of Flat Shapes which was carried out in class III SDN Sananwetan 2 did not appear to have carried out activities related to investigation and discovery. This can be seen from the learning outcomes obtained by class III students, namely from 25 students who achieved completeness only 7 students or 28%. In this case the teacher must conduct a classroom action research so that students get the expected results. The research was conducted using a learning method, namely Guided Discovery Learning, which is a method where in the teaching and learning process the teacher allows students to find information for themselves without being told or lectured, and the teacher acts as a facilitator.